2023
DOI: 10.1038/s41598-023-41634-z
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic aberration and spectral dependency of extended-range-of-vision intraocular lens technology

Grzegorz Łabuz,
Weijia Yan,
Isabella D. Baur
et al.

Abstract: This study compared the optical quality and chromatic performance of refractive-diffractive intraocular lenses (IOLs) that are designed to extend the range of vision of pseudophakic patients and alter chromatic aberration. Five IOLs were evaluated, Tecnis Synergy and Triumf POD L GF, both intended to compensate for eye's chromatism, as well as Acriva Trinova Pro C—a lens that increases chromatic aberration, and AT Lisa Tri and AcrySof IQ PanOptix. An optical setup composed of a corneal model inducing monochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The findings suggest that the imaging of the Symfony has a spectral dependence, which may cause a bias in the patient's color perception. The spectral dependence of the Symfony and some trifocal IOLs was also observed in other studies [ 28 , 29 ]. Contrary to this, no spectral dependence was observed in the through-focus images formed by the fabricated IOL.…”
Section: Discussionsupporting
confidence: 80%
“…The findings suggest that the imaging of the Symfony has a spectral dependence, which may cause a bias in the patient's color perception. The spectral dependence of the Symfony and some trifocal IOLs was also observed in other studies [ 28 , 29 ]. Contrary to this, no spectral dependence was observed in the through-focus images formed by the fabricated IOL.…”
Section: Discussionsupporting
confidence: 80%
“…Chromatic aberration may occur longitudinally or laterally 5–9 . When incident visible rays parallel with the axial plane propagate through a lens, the foci of lights with different colors may vary longitudinally along the optical axis.…”
Section: Chromatic Aberrationmentioning
confidence: 99%
“…Chromatic aberration may occur longitudinally or laterally. [5][6][7][8][9] When incident visible rays parallel with the axial plane propagate through a lens, the foci of lights with different colors may vary longitudinally along the optical axis. This type of color distortion phenomenon is referred to as longitudinal or axial chromatic aberration.…”
Section: Introductionmentioning
confidence: 99%
“…The reported LCA values for pseudophakic eyes range from 0.45 D to 1.45 D, which despite inter-subject variability, also depend on the lens model, the light spectrum, and the measurement procedure [10,11]. The increasing awareness of the magnitude of LCA in the pseudophakic population has led to the current trend among IOL manufacturers to correct the IOL's and eye's chromatism in presbyopia-correcting IOLs through a diffractive principle [12][13][14][15]. Laboratory studies have shown that such designs indeed reduce the impact of LCA on the polychromatic image quality when tested in a model eye [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing awareness of the magnitude of LCA in the pseudophakic population has led to the current trend among IOL manufacturers to correct the IOL's and eye's chromatism in presbyopia-correcting IOLs through a diffractive principle [12][13][14][15]. Laboratory studies have shown that such designs indeed reduce the impact of LCA on the polychromatic image quality when tested in a model eye [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%